NGO Efforts and Their Role in the Junior Doctor Plight - Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2023)
Over the years, we are faced with many issues surrounding junior doctors, as they make their way into the professional working platform. To address this matter, many non-governmental organizations (NGOs) have been actively involved to improve the welfare of the fraternity. Among one of the earliest and ongoing concerns frequently brought up is the House Officers (HO) wellbeing, which is said to be associated with high levels of stress leading to mental health problems, and sometimes leaving the medical profession altogether. In Malaysia, the number of HOs not completing training within the allocated time is slowly declining with dropout rates increasing yearly. This causes a lot of constraints on the HO, their family, sponsors, patients, and not to mention our healthcare system. There are many identified reasons for this matter, therefore, the Islamic Medical Association of Malaysia (IMAM)’s HO preparatory course was one of the pioneer courses organised to address this since its commencement in 2010. This module is frequently re-evaluated, and IMAM has actively pursued research on its effectiveness. Next, is the road crash injury among doctors in which IMAM has been involved in addressing this matter by actively seeking dialogues with stakeholders, organising campaigns, workshops and obtaining grants for research in the matter. IMAM on its own or in collaboration has consistently backed efforts to improve wellbeing of the healthcare fraternity. Other efforts include issuing press statements on concerns of unfair treatment of the contract doctors, addressing importance of mental state of doctors during the COVID 19 pandemic and reminding on the dangerous consequences of sleep deprived doctors. The NGO’s role, specifically in IMAM, apart from serving the community is also to be a voice for its members and associates for our overall safety, wellbeing, and the community we serve. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S15